Systematic Symptom Reporting by Pediatric Palliative Care Patients with Cancer: A Preliminary Report - Madden, Kevin (J Palliat Med, 2019)
Background: Systematic symptom assessment is not a standard of care in children with cancer. Many well-known symptom assessment tools are lengthy or difficult to integrate into a daily pediatric palliative care practice. We created a series of brief and simple questions to be systematically given to children and their caregivers. Objective: The primary objective was to determine the percentage of eligible children and caregivers exposed to the questions that were able to complete the assessment. Secondary objectives included documenting the symptom burden at the time of consultation, evaluating the level of agreement in symptom reporting between children and caregivers, as well as between children/caregivers and the referring medical team. Design: A series of systematic questions were presented to all caregivers (if present) and children who were seven years of age or older at the time of initial consultation with pediatric palliative care. Results: One hundred twenty-two consecutive children/caregiver dyads were given the survey. One hundred seven of 108 (99%) eligible caregivers and 83 of 97 (86%) eligible children completed the survey. Lack of appetite (child—72/83, 87%; caregiver—89/107, 83%) and pain (child—71/83, 86%; caregiver—86/107, 80%) were the most commonly reported symptoms. Caregivers reported irritability (p = 0.005) and nervousness (p < 0.001) more frequently than children. Referring medical teams significantly underdiagnosed psychological and other less clinically evident symptoms such as lack of appetite, fatigue, and sleep disturbance (p < 0.001). Conclusions: Our series of questions is easy to complete by children and caregivers. Systematic symptom assessment of children with cancer referred to palliative care should become a true standard of care.